Omnidirectional optical spectra for a nanocomposite cholesteric elastomer. (28th May 2019) - Reyes, Guillermo; Reyes, J Adrian
Abstract: We perform a theoretical model for studying the propagation of electromagnetic waves, within a cholesteric elastomer slab, doped with metallic inclusions aleatorily distributed, whose corresponding dielectric properties can be expressed in terms of a resonant effective uniaxial tensor. We have obtained an omnidirectional narrow conducting band and two narrow reflection bands created in the optical spectrum for right and left circularly polarized light, as well as narrow reflection bands for right circularly polarized light. We have found that the transmission and reflection spectra depend on light incidence angle and the filling fraction of metallic inclusions.